Making the law work for everyone: legal empowerment in public schools / Mohd Haris Abdul Rani - Abdul Rani, Mohd Haris (Faculty of Administrative Science and Policy Studies, 2014)
Legal education is not meant for law students alone. It is for the mass public. Law contain rules and regulations which target principally towards the proper administration of the general public. Basically, law entails legal rights and duties of all citizens, therefore lacking this crucial knowledge, social justice is meaningless. Society would not be able to achieve the ultimate structural harmony it hopes to establish. Disputes will keep on increasing and court cases will multiply. Sentencing and remedies clouds the society. The legal maxim Ignorantia Juris Non Excusat (ignorance of the law excuses no one) should be seen as an encouraging the enhancement of legal consciousness rather than a negative connotation of it. Global society lacks this legal knowledge and awareness which are the critical tool to overcome many legal issues faced throughout their life. Current legal awareness of most people is more about knowledge of procedural rules as compared to substantial laws, which in reality, are more significant. It is the aim of this paper, to investigate this unrealized stigma of the society. This exploratory research invites future research, qualitative or quantitative methods, in discovering the possibility of implementing such awareness program in schools via the proposed ‘empowerment model’ using the reflexive law concept. The model is expected to enhance the empowerment of law in the society by ensuring that law knowledge is for everyone and not only for a certain segment of the population. The paper concludes that even though legal illiteracy is a social fact, there are great possibilities for further research towards acknowledging and substantiating the importance of empowering the public in legal education in achieving a global social legal justice.